The Dynamics of Credit Procyclicality and Stability of Macroeconomics in Indonesia - Lestari, Ni Putu Nina Eka; Budhi, Made Kembar Sri; Sudama, I Ketut; Suasih, Ni Nyoman Reni; Taun, I Nyoman (Jurnal Ekonomi Kuantitatif Terapan, 2021)
Credit growth is one of the important indicators of the financial system that can drive the country economic growth, but on the other hand credit growth can also cause risks in the financial system due to the economic actors’ moral hazard. The purpose of this research is to analyze the credit procyclicality pattern and economic growth in Indonesia. In addition, this study aims to determine the relationship pattern between credit and some macroeconomic variables. The method used is VECM with quarterly time series data during 1998 until 2016. The analysis shows that credit growth and economic growth have positive causality. This shows pro-cyclicality between credit and economic growth in Indonesia. However, in the long run this pattern shows a downward trend although still positive and permanent, which means that excessive credit growth can also lead to a decline in economic growth.